Breaking with traditional models: how genzs´ approach to marriage will impact the engagement ring market in Europe - Sillem, Marie-Lou (2021)
The aim of this project is to analyse the legal and emotional approach to marriage of the future generation of buyers. Does the engagement ring market still play a relevant role in Europe for the next generation of customers? To guarantee a relevant result for the fine jewelry industry, interviews with the targeted generation were conducted. This study showed that the engagement ring market will play a relevant role, as will marriage, provided that the market players adapt to the new traditional models sought by GenZ.